(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The success of athletes in high-level sport competitions is an important component of the country’s international prestige. In this regard, the situation regarding the importance of the health of athletes for their achievement of high sports results has acquired particular relevance [4; 17; 19]. The results of scientific research have proven that the optimal health indicators of athletes are based on the state of dynamic balance between the functional reserves of the body and the factors affecting it [1; 9; 22; 23]. At the same time, the magnitude of the influence of the factors that are inherent in the modern system of training athletes on the body of those involved increases in proportion to the stages of their professional development, which requires not just optimal health indicators, but the presence of an appropriate level of reserves of functions of its components [7; 12; 26]. The value of the latter is the basis of the athlete’s reliability - an indicator that is characterized by high performance of actions and its stability in extreme conditions of activity [5].